Designing Punthuk Setumbu as a Romanticism Landmark based on Film-Induced Tourism - Erviana, Vera Yuli; Wibowo, Arif Ardy; Akhsan, Rifai Nur (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Punthuk Setumbu is a natural beauty located in Karangrejo Village, Borobudur, Magelang Regency. The popularity of Punthuk Setumbu has surged following its use in the film Ada Apa Dengan Cinta 2, establishing it as a frequently visited tourist destination. The significant potential of Punthuk Setumbu necessitates effective management to enhance its tourist appeal while preserving its natural integrity. This community service program seeks to elevate the knowledge and abilities of partners in the following area such as: concept and functionality of photobooths, creation and implementation of the photobooth. The solutions provided by this community service encompass the dissemination of the design assistance, and photobooth deployment. The activities will be conducted via training employing lectures and practical exercises for the partners. The program includes phases of socialization, workshops, and activity monitoring. These training garnered favorable evaluations, with all aspect are increase for photo booth training. The implementation of the activities will occur between October 2024 and January 2025. The evaluation results demonstrate an enhancement in participants' knowledge regarding photo booth and film-induced tourism. This training aims to enhance Punthuk Setumbu's appeal to tourists and elevate regions income